2014
DOI: 10.1007/s00268-014-2483-5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Result and Overall Satisfaction after Minimally Invasive Video‐assisted Thyroidectomy (MIVAT) versus Robot‐assisted Transaxillary Thyroidectomy (RATT): A Prospective Randomized Study

Abstract: RATT seems not to supersede MIVAT in terms of satisfaction when comparing two groups of patients undergoing thyroidectomy for benign disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 66 publications
1
26
0
2
Order By: Relevance
“…From this review not all the step are described, sometimes the working space and the docking time are considered together, other author in the total operative time do not consider the docking [20], so that it is difficult to know which is the step more time-consuming and technically demanding. The outcomes results comparable to other conventional technique in terms of postoperative hypocalcemia, recurrent laryngeal nerve palsy, definitive laryngeal nerve, and hospital length stay [27•].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this review not all the step are described, sometimes the working space and the docking time are considered together, other author in the total operative time do not consider the docking [20], so that it is difficult to know which is the step more time-consuming and technically demanding. The outcomes results comparable to other conventional technique in terms of postoperative hypocalcemia, recurrent laryngeal nerve palsy, definitive laryngeal nerve, and hospital length stay [27•].…”
Section: Discussionmentioning
confidence: 99%
“…Lallemant [17] described the cosmetic results of the scar and 16 patients on a total of 20 were either satisfied or very satisfied. Materazzi [20] with a patient scar assessment questionnaire compare two different thyroid techniques: the RATS and the minimally invasive video-assisted thyroidectomy (MIVAT). The appearance and satisfaction with scar appearance scores significantly favored MIVAT.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably the reason behind the surprising result obtained when MIVAT was compared to robot-assisted trans-axillary thyroidectomy. In an ironic twist, what was originally developed to be "a thyroid surgery free of a neck scar" was not superior to MI-VAT in terms of patient's satisfaction (34). Furthermore, there is no unnatural neck extension, no subplatysmal flap elevation, and no strap muscle transection in MIVAT.…”
Section: Mivat's Advantagesmentioning
confidence: 99%
“…The evidence for this is level 1b as in addition to the several case control and cohort studies evaluating patient-reported outcome measures [1, 28-30], there is also a randomised controlled trial to support this though the latter failed to demonstrate cosmetic superiority of the transaxillary robotic approach over minimally invasive video-assisted thyroidectomy [17]. …”
Section: Benefitsmentioning
confidence: 99%
“…The feasibility and safety of robotic thyroidectomy are not limited to studies from the Far East (where the majority originate), but also from high-volume centres in the UK, Europe, and North America [1, 15-17]. …”
Section: The Evidence Basementioning
confidence: 99%